Efisiensi Lighting Dan Rendering Dalam Film Pendek Animasi 3d Bed Time Story - Christian Aditya (Universitas Multimedia Nusantara, 2015)
Light, Everything we currently, ever, or will see in the world, the fact is due to the presence of light. without light there is no color, shape, and of course we cannot distinguish the material, distance, and the nature of the object when not it’s not illuminated by light. Therefore the author felt it is important to discuss about lighting, especially for applications in the author’s field of interest, 3D Animation. In this journal, will be found an alternative to a more efficient way to do lighting and rendering in 3D animation projects using a variety of theories and basic knowledge of light. Keywords: Bed Time Story, animation, 3D, lighting, rendering